2019
DOI: 10.1631/jzus.b1900075
|View full text |Cite
|
Sign up to set email alerts
|

Changes in peripheral blood inflammatory factors (TNF-α and IL-6) and intestinal flora in AIDS and HIV-positive individuals

Abstract: Objective: In this study, we investigated the changes in peripheral blood inflammatory factors and intestinal flora in acquired immune deficiency syndrome (AIDS) and human immunodeficiency virus (HIV)-positive individuals (AIDS/HIV patients), and explored the relationships among intestinal flora, peripheral blood inflammatory factors, and CD4 + T lymphocytes. Methods: Thirty blood and stool samples from an AIDS group and a control group were collected. The levels of tumor necrosis factor-α (TNF-α) and interleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
0
13
0
2
Order By: Relevance
“…In another study, the results indicated that deficiencies of IL-10, IL-10Rα and IL-10Rβ may result in dysbiosis of the caecal microbiota in mice, characterized by expanded populations of opportunistic bacteria of the families Enterococcaceae and Enterobacteriaceae ( 67 ). In patients with immune deficiency syndrome, the amount of Enterococcus faecalis was positively correlated with the contents of TNF-α and IL-6 and the CD4 + T-lymphocyte count ( 68 ). In patients with liver cirrhosis, the level of Enterococcus has also been indicated to be positively correlated with AST levels (P<0.05) and Bifidobacterium was negatively correlated with AST (P<0.05) ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the results indicated that deficiencies of IL-10, IL-10Rα and IL-10Rβ may result in dysbiosis of the caecal microbiota in mice, characterized by expanded populations of opportunistic bacteria of the families Enterococcaceae and Enterobacteriaceae ( 67 ). In patients with immune deficiency syndrome, the amount of Enterococcus faecalis was positively correlated with the contents of TNF-α and IL-6 and the CD4 + T-lymphocyte count ( 68 ). In patients with liver cirrhosis, the level of Enterococcus has also been indicated to be positively correlated with AST levels (P<0.05) and Bifidobacterium was negatively correlated with AST (P<0.05) ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bifidobacteria are commensal microorganisms of the human GI tract and are thought to play pivotal roles in maintaining human health. Moreover, studies have shown that Bifidobacteria can significantly inhibit TNF-α and IL-6 levels ( Lu et al., 2019 ; Nie et al., 2020 ). In the present study, we found that the abundance of Bifidobacterium in patients with primary HSP was higher than in patients with recurrent HSP but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-articular injections of IL-6 reproduced OA-like cartilage lesions in mice, and IL-6 knockout (KO) mice develop less severe posttraumatic OA lesions [50]. Lu J, et al investigated that correlation between the amount of intestinal ora and the number of CD4 + T lymphocytes and the levels of TNF-α and IL-6 [51]. In our study, we found that antibiotics reduce the in ammatory response throughout the body after inhibiting the intestinal ora.…”
Section: Discussionmentioning
confidence: 99%